Hand Hygiene Practices and Infection Control Measures among Emergency Units Health Care Providers - Anees Flayyih Abdulhassan1 , Sahar Adham Ali2 (Institute of Medico-legal Publications Pvt Ltd, 2020)
Background: Emergency units is a main part for hospital admission. It is the front line of the healthcare systems in the response to emergencies and public disasters, so the infection preventive measures practices can be easily overlooked or neglected by immediate and life threatening issues. Objectives: To assess the practices of health care providers regarding hand hygiene. Methodology: A descriptive cross-sectional study design carried out from the period between (Sep. 2018 to Aug. 2019). The study has been conducted in the emergency units at Al-Hilla teaching hospitals. Non probability (purposive) sample of (125) health care providers who work in the emergency unit were selected, (110) nurses, (15) physicians were selected related to special criteria. Special checklist prepared, inter observer reliability calculated the statistical results recorded (r: 0.90), which is statistically accepted. Results: The results shows that the higher percentage of the study sample 104 (83.2%) were between (20- 30) years age group, 73 (58.4%) were male, while most of the study sample 67 (53.6%) were Bachelor or postgraduate degree holder, related to the study sample marital status, the higher percentage 64 (51.2%) were married. Overall hand washing practices which consider as the most important measures to control of infection were poor (1.61 0.748). Conclusion: Regarding to the healthcare providers practices in hand washing with respect to the infection control measures during their daily caring in the emergency units the statistical results show low level of practices. Recommendation: Effective educational program should take place for all healthcare providers by task based strategies to utilize the practices include bedside procedures.